Pemberdayaan Petani Jagung oleh Stakeholders di Nagari Kataping Kecamatan Batang Anai Kabupaten Padang Pariaman - Deni Ardila; Fitri Eriyanti (Faculty of Social Science, Universitas Negeri Padang, 2019)
The purpose of this study was to determine the inhibiting factors and forms of empowerment of corn farmers by Stakeholders in nagari Kataping Kecamatan Batang Anai Kabupaten Padang Pariaman. The backround of this research is that there are still many nagari Kataping communities who do not yet know how to process corn after harvest. This research uses qualitative research methods with descriptive type. The technique of this research is purposive sampling. The informants of this guidelines the form of structured questions and documentation. Data validity test in this study uses data source triangulation techniques because the comparison and back-checking of the degree of information obtained through different sources. Data analysis techniques throught three stages, namely the stage of data reduction, the stage of data presentation, and the stage of drawing conclusions. The results of this study are the forms of empowerment of corn farmers by Stakeholders and the inhibiting factors for the cultivation of corn farmers by Stakeholders in the nagari Kataping Kecamatan Batang Anai Kabupaten Padang Pariaman.